Perfluoroalkyl Substances are Inversely Associated with Coronary Heart Disease in Adults with Diabetes - Honda-Kohmo, Kyoko (J Diabetes Complications, 2019)
AIMS: Perfluoroalkyl substances (PFAS) are environmentally and biologically persistent synthetic environmental contaminants linked to adverse health outcomes. Though null to modest inverse relationships between PFAS and coronary heart disease (CHD) have been reported, studies regarding relationships in high risk populations such as those with diabetes are sparse. We investigated the relationship of PFAS with CHD in persons with diabetes. METHODS: Data on 5,270 adults, aged ≥20 years, with diabetes were obtained from the C8 Health Project. Four PFAS were investigated separately: perfluorohexane sulfonate (PFHxS), perfluoroctanoic acid (PFOA), perfluorooctane sulfonate (PFOS), and perfluoronanaoic acid (PFNA). RESULTS: In logistic regression analyses adjusting for age, sex, diabetes duration, BMI, smoking, lipids, WBC, CRP, eGFR, uric acid, hemoglobin and iron, all PFAS were inversely associated with CHD, ORs (95% CIs) : PFHxS; 0.72 (0.65-0.79), PFOA; 0.90 (0.81-0.96), PFOS; 0.90 (0.81-0.99), PFNA; 0.88 (0.76-1.02). Stratification by chronic kidney disease status revealed similar inverse relationships for those with and without chronic kidney disease. CONCLUSIONS: In this cross-sectional study of over 5,000 adults with diabetes, PFAS showed inverse associations with CHD. These findings may, if confirmed in future studies, provide new physiologic understanding of CHD prevention strategies.